Формування професійної компетентності майбутніх педагогів в умовах магістратури: теоретичний аналіз проблеми - Матвеєва, Наталія; Матішак, Маріанна; Matveyeva, N.; Matishak, M. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті автори виокремлюють основні завдання освітньої галузі на сучасному етапі, наголошуючи на потребі підготовки висококваліфікованих педагогічних кадрів. Під час навчання в магістратурі формуються професійні риси, якості та вміння, удосконалюється майстерність майбутнього педагога. Метою статті є теоретичне обґрунтування та вивчення ефективності науково-педагогічних умов формування професійної компетентності майбутніх педагогів у процесі магістерської підготовки. Для підвищення якості навчання необхідно реформувати освітній процес вищого навчального закладу, підвищити якість навчання, створити науково-педагогічні умови, які б забезпечили високу ефективність професійної підготовки майбутніх магістрів. Автори стверджують, що особливе місце у навчально-виховному процесі набуває компетентнісний підхід, що дозволяє формувати професійно мобільного фахівця з високим загальним, культурним та професійним рівнем, готового до змін, систематичного самовдосконалення та самореалізації. In the article, the authors singled out the main tasks of the educational branch at the present stage, stressing the need for the training of highly skilled pedagogical staff. It is emphasized that formation of professional competence is one of the priorities of the national education system. The purpose of the article is to substantiate theoretically and to explore the effectiveness of scientific and pedagogical conditions of formation of future teachers’ professional competence. The essence of such concepts as «professional mobility», «professional competence» and «self-development» has been grounded in the article. The authors analyzed scientific psychological, pedagogical and methodological literature concerning the disclosure of these concepts. The article is a consideration of various points of view and scientific positions on the problem of professional competence formation in students at higher educational institutions from the vantage point of the competency-based approach. It presents and generalizes the content of the main notions in the terminological apparatus of the competency-based approach and ways of professional competence formation in students as a result of their professional preparation. The authors argue that a special place in the educational process acquires a competent approach that allows the formation of a professionally mobile specialist with a high general, cultural and professional level, ready for change, systematic self-improvement and self-realization.
Forming of the professional competence of the future teacher in the process of preparation of the master: theoretical analysis of the problem
Keywords: професійна підготовка; професійна мобільність; майстерність; професійна компетентність; професійне становлення; саморозвиток; professional training; professional mobility; skills; professional competence; professional formation; self-development